Muharram Fest Berbasis Madrasah Diniyah Takmiliyah Desa Ngerjo Kecamatan Ringinarum Kabupaten Kendal - Lutfiyah Lutfiyah; Ikrima Putri Amharina; Muhammad Fawaid (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Muharram the beginning of the Hijriyah month is celebrated with various activities. One of which is holding competitions in the field of education. Competitions with religious nuances which are usually held, apart from being a form of commemoration and celebration, are also a means of learning and self-development for children. Muharram competition activities are carried out through four stages, namely planning, implementation, competition and awards. In preparation, the KKN team formed a committee structure to clearly distribute tasks. The madrasah also helped the committee with several competition preparation needs. In general, the Muharram Fest competition held by the KKN team went well and smoothly. It is hoped that holding this competition will be useful as a means of learning and self-development for the students of Madrasah Diniyah Takmiliyatul Ula, Ngerjo Village. Can encourage them to have a passion for learning and self-confidence. Then, it is hoped that the next KKN Team will be able to learn lessons from the various shortcomings that existed during the process of organizing the Muharram Fest competition by this KKN group.